Enhanced Therapeutic Treatment of Colorectal Cancer Using Surface-Modified Nanoporous Acupuncture Needles. Issue 1 (December 2017) - Lee, Bo; Kim, Hye-Rim; Choi, Eun-Sook; Cho, Jung-Hoon; Kim, Nam-Jun; Kim, Jung-Hee; Lee, Kyeong-Min; Razzaq, Abdul; Choi, Hansaem; Hwang, Yunju; Grimes, Craig; Lee, Bong-Hyo; et al.
Abstract Acupuncture originated within the auspices of Oriental medicine, and today is used as an alternative method for treating various diseases and symptoms. The physiological mechanisms of acupuncture appear to involve the release of endogenous opiates and neurotransmitters, with the signals mediating through electrical stimulation of the central nervous system (CNS). Earlier we reported a nanoporous stainless steel acupuncture needle with enhanced therapeutic properties, evaluated by electrophysiological and behavioral responses in Sprague-Dawley (SD) rats. Herein, we investigate molecular changes in colorectal cancer (CRC) rats by acupuncture treatment using the nanoporous needles. Treatment at acupoint HT7 is found most effective at reducing average tumor size, β-catenin expression levels, and the number of aberrant crypt foci in the colon endothelium. Surface modification of acupuncture needles further enhances the therapeutic effects of acupuncture treatment in CRC rats.